Determinant of Millennial Generation Work in Agricultural Sector West Java Province - Ruslan, Januar Arifin; Mutolib, Abdul; Pramita, Dira; Rofatin, Betty; Hartoyo, Tedi (East Asian Journal of Multidisciplinary Research, 2024)
Phenomenon of decreasing workers in agricultural sector has an impact on sustainability of agricultural businesses, one of which is in West Java Province. Role of millennial generation is expected to participate in agricultural businesses. This study analyzes determinant of millennial generation work in agricultural sector West Java Province. Sample in this study was number of millennial farmers (19-39 years) according to area in West Java Province. Data were analyzed using multiple regression models. Results showed that the level of education of a region and the characteristics of the region influenced the number of millennial farmers in West Java Province. The level of education has a negative effect and the characteristics of the region shows the difference in the number of millennial farmers in West Java Province.